A succinct technique for the extraction of the proximal femoral nail anti-rotation (PFNA) after unlocking failure: a case report - Cao, Ming-de (J Orthop Surg Res, 2020)
INTRODUCTION: Proximal femoral nail anti-rotation (PFNA) is a routine method to deal with intertrochanteric fractures in the elder population. It is challenging to remove PFNA in some cases as a result of stripping of blade heads. In this case presentation, we describe a novel technique using commonly available instruments that can be used to remove stripped, even broken anti-rotation blade where conventional methods have failed. METHODS: The subject underwent a PFNA removal surgery 15 months after the previous fixation. We encountered difficulties using the regular instrument to remove the anti-rotation blade. A 5-mm tungsten carbide bur was used to drill a single cortical hole at the end of the blade. Then double-strand steel wire was threaded through the hole, and the distal part was shaped into a circle which could tie to the extraction screw. Slide Hammer was applied to gently knock out the blade along the anatomical direction of the femoral neck. RESULTS: The technique helped us successfully remove the anti-rotation blade and provided the patient with a satisfactory result. CONCLUSION: The use of a tungsten reamer and steel wire loop to remove the proximal femoral anti-rotation blade may provide a cost-effective and straightforward method of dealing with extraction failure.